Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species - Şi̇ri̇n Deni̇z; Taylan Mehmet Sai̇t; Sevgi̇li̇ Hasan; Mol, Abbas (Zootaxa, 2019)
The genus Saga is a genus of generally large predatory bush-cricket species. It includes 13 taxa in the Palaearctic region. In this research, eight species belonging to Saga (Tettigoniidae, Saginae) were sampled during field studies in different regions of Anatolia of Turkey between 2010 and 2018 (except one specimen). The bioacoustic parameters of these species recorded during the field or in laboratory conditions and the male calling song descriptions, as well as the oscillographic illustrations and distribution maps are given. A new population of Saga found from the South-Eastern Taurus (Hakkari province), which is affiliated to a new species and shows similarity to S. ephippigera, along with the morphological and bioacoustical descriptions of Saga hakkarica sp. n. Şirin & Taylan from Turkey, are also given. The relationships between the new species and the closest taxa are discussed using morphological and bioacoustical characters. The structural investigations of the male calling songs reveal three different bioacoustic groups affiliated to eight Anatolian Saga species; as (i) Ephippigera group (S. syriaca + (S. ephippigera + Saga hakkarica), (ii) Natoliae group (S. natoliae + (S. beieri + (S. longicaudata + S. puella) and (iii) S. cappadocica.